Applied approach to privacy and security for the internet of things - Chatterjee, Parag 1992; Benoist, Emmanuel 1972; Nath, Asoke 1953 (IGI Global/Information Science Reference, 2020)
"This book examines the conceptual aspects of security and privacy in IoT. It also explores the application of IoT systems in smart transports, smart cities, and smart healthcare"